STUDI KARAKTERISTIK KOMPOSIT SERAT BAMBU DENGAN MATRIKS EPOKSI VARIASI FRAKSI VOLUME SERAT SEBAGAI MATERIAL ALTERNATIF PEREDAM SUARA RUANGAN - Tamam Fadlurahman (2022)
Composite is a combination of two or more types of material which will then produce new characteristic properties. Natural fibers such as bamboo apus can be used as a type of reinforcement in the process of making composites. Volume fraction is an important aspect in producing new characteristic properties so that variations in volume fraction must be considered to obtain more optimal results. The sound attenuation test is a test to determine the decibel value (db) using the Audio Frequency Generator at the Physics Lab, Universitas Pembangunan Nasional Veterans Jakarta. Silencer as an alternative to the process of making this composite by doing sound attenuation testing so as to produce a Noise Absorption Coefficient (NAC) where the value range is = 0.25 - 1. Minimum = 0.25. In apus bamboo fiber with epoxy resin with various volume fractions of 15%, 25% and 35% composites, the 15% composite has a more optimal value than the 25% and 35% composites. The 15% composite has the most optimal average value with a coefficient value ( 0.3118 then the second highest average value is obtained in the 25% composite with a value of 0.2588 and the last average value is obtained at the 35% composite with a value of 0.2581.